The Relationship Between Anxiety and Adverse Events During Hematopoietic Stem Cell Transplantation in Cancer Patients: A Cross-Sectional Study (Bangladesh Journal of Medical Science, 2024)
Objective Anxiety, negatively affects the response to transplantation and the recovery process after transplantation. Anxiety prevalence is high pre and post transplantation but no information is known about during transplantation. This study was conducted to determine anxiety and adverse events during hematopoietic stem cell transplantation (HSCT) and to explain the association between these two conditions.Methods The sample consisted of 93 patients with cancer who received hematopoietic stem cell transplantation at the Bone Marrow Transplant Centre in Türkiye. The data were collected using a patient information form and the State Anxiety Inventory (STAI-S). Significance between the descriptive characteristics of the participants and the scale was calculated using a one-way ANOVA and Student-T test. Logistic regression analysis was performed to determine the effect of adverse events on the level of anxiety.Results We found that there was a significant difference between the variables of age (F = 2.497 p = 0.020), gender, years after diagnosis (F= 1.381 p = 0.035), the state of believing that transplant will be successful and previous transplant history, and the STAI-S mean score. The Nagelkerke R2 value of the model was 0.167. The goodness of fit of the model was assessed using Hosmer and Lemeshow’s test (X2 = 8.900, p = 0.203). When analyzing the adverse events during HSCT that affected the occurrence of anxiety, we found that nausea and vomiting increased the anxiety score by 6.1-fold (β: 0.613, p = 0.010), abdominal pain by 4.4-fold (β: 0.449, p = 0.030), and tachycardia by 2.6-fold (β: 0.267, p = 0.020).Conclusions The results of this study showed that patients experienced nausea and vomiting, hypertension and abdominal pain during stem cell transplantation, respectively; anxiety level was above the moderate level; nausea and vomiting, abdominal pain and palpitations increased anxiety. Preventing anxiety during stem cell transplant can reduce adverse effects depend on HSCT.Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 447-454